The first horseman - Case, John (New York : Fawcett Columbine, 1998)
An outbreak of Spanish flu in North Korea raises fears the virus is being tested as a weapon by the military. Early this century the flu killed millions and the U.S. races to find an antidote, seeking the virus in corpses which were buried in permafrost.
Keywords: Biological warfare -- Fiction; Detective and mystery fiction